OPTICAL METHOD FOR STUDYING HETEROGENEOUS SMOKE PLASMA - Римашевський, Олександр (SWorldJournal, 2025)
The problem of recording the ordered structure of the dispersed phase in plasma formations is reviewed. It is shown that in experiments with gas-discharge plasma containing monodisperse particles, “plasma crystals” were detected. A method for studying the